Strategi Social Media Marketing Instagram RFAS Music dalam Peluncuran Lagu “Berona” Karya Rizky Febian - Fadhilah Medy Putra Ramadhan; Agus Hermanto (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
Social media provides significant benefits in life, one of which is as a communication and promotional tool. Instagram, as the platform with the second most users in the world, is a strategic medium for promotion. This study analyzes RFAS Music's strategy in utilizing Instagram to promote the song